Happiness before and after an election: An analysis based on a daily survey around Japan's 2009 election - Yusuke Kinari; Fumio Ohtake; Miles Kimball; Shoko Morimoto; Yoshiro Tsutsui (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This paper investigates whether the Japanese voters became happy and/or unhappy due to the results of the General Election in 2009. We conducted a daily web survey for seven days before and after the election, obtaining1068 responses. Estimating a fixed effects model, we found that supporters of the Democratic Party of Japan (DPJ), the winner, became significantly happier, and supporters of the Liberal Democratic Party of Japan (LDP) and New Komeito, the losers, became significantly unhappier on the day following the election. However, happiness returned to the previous level in one or two days, implying people adapted to the news very quickly. Dividing those who support the policies of DPJ into two groups, those who expect material benefits from the victory of DPJ and those who do not, we demonstrated that the reason why the supporters of the winner (DPJ) felt happy was not because they obtained material benefits from the change of government. We also found that the happiness level of those whose expectation of the election results were realized did not change, while that of those whose expectation differed from the reality changed substantially. In a word, only unexpected results matter.
Keywords: I31; D72; 330; happiness; election; expectation; survey; Japan